Genetic Variability and Relationship among Pumpkin Landraces (Cucurbita moschata L) of Assam, India - Khirud Panging; Gobin Candra Bora; Debojit Sarma; Trishna Taye; Akashi Sarmah (Current Research Progress in Agricultural Sciences Vol. 1, 2024)
The variability present in the population could be useful inheritable components with the aid of genetic parameters such as genotypic variance, phenotypic variance, heritability, genotypic co-efficient of variation and genetic advance which serve as a basis for effective selection. The production of pumpkin in India is mainly used for domestic consumption as a fresh vegetable. Being a source of vitamin A, pumpkin can play an important role in the fight against vitamin A deficiency and it might improve certain functions of the immune system. Thirty diverse landraces of pumpkin comprising from eight districts of Assam viz., four landraces from each district, Sivasager, Dibrugarh, Karbi Anglong, Haflong, Jorhat & Majuli and three landraces from each Lakhimpur and Kokrajhar. The landraces were subjected to analyses of variance and covariance for the estimation of genetic variability parameters and correlation coefficients among the 19 characters. The experiment was carried out during the rabi season of 2017-18 at the Instruction Cum and Research (ICR) Farm of Assam Agricultural University in a Randomized Block Design with three replications. From the analysis of variance, it was recorded that the presence of variation among thirty pumpkin landraces for all characters. The highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were recorded for single fruit weight with 51.47 per cent and 54.88 per cent, indicating the presence of greater variability for the trait. The heritability in the broad sense was recorded highest for the petiole length. The GA calculated as per cent of the mean was recorded for single fruit weight (99.44%), followed by yield per plant. In character association five traits namely petiole length (0.294), fruit length (0.273), fruit diameter (0.309), flesh thickness (0.357), and single fruit weight (0.902) were positively correlated with fruit yield per plant out of 18 characters. The high estimates of heritability were observed for vine length, leaf blade length & breadth, total chlorophyll content, petiole and peduncle length, and days to first flowering. The high genetic advance was observed for single fruit weight and fruit yield per plant, indicating a predominance of additive gene effects and possibilities of effective selection for the improved characters.